A novel methodology for indirect application of hydrophobic agents into cement matrix: Superabsorbent polymers (SAPs) as a delivery medium - Dalia Bednarska; Alicja Wieczorek; Julia von Werder (Case Studies in Construction Materials, 2025)
Hydrophobic agents are one of the most commonly used means of prolonging the lifespan of cement-based materials. However, when water-repellent is added to the batch water it can interfere with cement hydration leading to deteriorated mechanical properties of the hardened material. To eliminate this drawback, a novel methodology of indirectly applying hydrophobic agents to cement-based materials is introduced. The presented approach uses super absorbent polymers (SAPs) as a delivery medium. SAP containing water-repellent is added to the fresh cement mixture, which ensures a gradual release of the admixture. The release is driven either by drying which generates moisture gradient or by compression of polymer particles by hydrates arising in their vicinity. Such mechanisms lead to a delayed dosage of the hydrophobic agent, which is when the partially hardened cement matrix is less vulnerable to interference compared to the fresh mixture. The effectiveness of the proposed methodology was verified in the extensive experimental program. Cement mortars of two water-to-cement ratios (0.4, and 0.5) were tested in terms of compressive strength, capillary absorption, and contact angle among others. Based on the obtained results it is concluded that the proposed methodology limits the negative impact of the hydrophobic agent on cement hydration. The mechanical performance of the samples modified with the indirectly dosed admixture is improved compared to the conventionally hydrophobized material in each analysed case. The results of isothermal calorimetry support the thesis. Additionally, the effectiveness of imparting hydrophobic characteristics to the cement matrix was as good as in the case of the conventional dosing. The mercury intrusion porosimetry, as well as thermogravimetric tests, were run to provide a deeper insight into the microstructure and composition of the modified material. Scanning electron microscopy was used to give a better insight into samples’ morphology. The novel methodology presented can also potentially be used to dose other types of admixtures that can interfere with cement hydration.